Improving the Stability of the Passenger Vehicle by Using an Active Stabilizer Bar Controlled by the Fuzzy Method - Tuan Anh Nguyen (Complexity)
The rollover phenomenon is a particularly dangerous problem. This phenomenon occurs when the driver travels at high speed and suddenly steers. Under the influence of centrifugal force, the body vehicle will be tilted and cause the wheels to lift off the road. To solve this problem, the method of using an active stabilizer bar has been proposed. The active stabilizer bar is controlled automatically by a previously designed controller. The performance of the active stabilizer bar depends on the selected control method. Previous research often only used a half-car dynamics model combined with a linear single-track dynamics model to simulate the vehicle’s oscillation. In addition, most of the research focuses only on the use of linear control methods for the active stabilizer bar. Therefore, the performance of the stabilizer bar is not guaranteed. This paper focuses on establishing the model of spatial dynamics combined with the nonlinear double-track dynamics model that fully describes the vehicle’s oscillation most accurately. Besides, the fuzzy control method is proposed to control the operation of the hydraulic stabilizer bar. This is a completely novel model, and it is suitable for the actual traveling conditions of the vehicle. Also, simulations are done based on different scenarios. The results of the paper showed that the values of the roll angle, the difference in the vertical force at the wheels, and the displacement of the unsprung mass were significantly reduced when the vehicle used the active stabilizer bar, which is controlled by an intelligent control method. Therefore, the stability and safety of the vehicle have been guaranteed. This result will be the basis for performing other more complex research in the future.